(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In the novel Raag Darbari, Shrilal Shukla clearly depictsthe picture of post-colonial Indian political scenario which is dominated bycertain sectarian interests, motives and evil political practices. This novelas a political satire clearly reveals the real face of India through image ofthe village Shivpalganj. In India the political domain is not an independentone because our political field is closely associated with certain social,religious, cultural and economic institutions. In our country the post-colonialpolitical leaders and political institutions are deeply influenced by theseinstitutions. By using this novel as a weapon, Shrilal Shukla criticise thesekinds of political and social issues and he summons the whole India for acomplete change in all fields of life. The picture of Shivpalganj stands forthe typical Indian village which is very much alienated and neglected by themodern developments and more civilised ‘modern Indian citizens’. In our countryfrom a school child to a well-known political leader everyone daily uses thewords like development, modernity, justice, equality etc... to point out theprogress of our nation but it is very hard to accept the truth that majority ofthe Indian villages and village people are still follow a ‘primitive tradition’which is f ull of supernatural beliefs, evil social practices and patheticeconomic conditions. As a visionary writer Shrilal Shukla, declares the truth thatthe change has to be made from the bottom of the society. Both the social andeconomic development in the main stream of our country has to make a greatinfluence on the alienated villages all over India that is why, Mahatma Gandhionce said that “India lives in its villages”.